1995
DOI: 10.1016/0168-6445(95)00012-2
|View full text |Cite
|
Sign up to set email alerts
|

Clostridial strain degeneration

Abstract: Strain degeneration, the loss of the capacity to produce solvents and form spores, typically occurs when Clostridium acetobutylicum and related clostridia are repeatedly subcultured in batch culture or grown in continuous culture, as opposed to being grown from germinated, heat-treated spores. Several mechanisms for degeneration have been identified thus far. (i) Degeneration can be caused by excessive acidification of the culture during exponential growth. We present data interpreted to mean that C. beijerinc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
31
0

Year Published

2001
2001
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(33 citation statements)
references
References 27 publications
2
31
0
Order By: Relevance
“…This is in agreement with Kashket and Cao, who concluded that heat‐shock directly selects for non‐degenerated cells while lowering the incubation temperature decreases the growth rate and thus the rate of acidification of the medium, allowing the sporulation pathway to be induced fast enough to outcompete degeneration. However, some degeneration resistant mutants have been isolated, which imply that the decrease in degeneration may not simply be due to decreased growth rate and acidification but a global gene regulatory mechanism may also play a role in strain degeneration (Kashket and Cao 1995). We were able to recover the sporulation ability of degenerated C. hungatei and Clostridium sp.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is in agreement with Kashket and Cao, who concluded that heat‐shock directly selects for non‐degenerated cells while lowering the incubation temperature decreases the growth rate and thus the rate of acidification of the medium, allowing the sporulation pathway to be induced fast enough to outcompete degeneration. However, some degeneration resistant mutants have been isolated, which imply that the decrease in degeneration may not simply be due to decreased growth rate and acidification but a global gene regulatory mechanism may also play a role in strain degeneration (Kashket and Cao 1995). We were able to recover the sporulation ability of degenerated C. hungatei and Clostridium sp.…”
Section: Discussionmentioning
confidence: 99%
“…Past efforts to harvest clean spores from such a mixture have been unsuccessful (Collier 1957;Zoha and Sadoff 1958). Another challenge to spore production is due to a process known as strain degeneration (Kutzenok and Aschner 1952;Kashket and Cao 1995), where loss of spore production occurs after repeated subculturing or during growth in continuous culture (Kashket and Cao 1995). Degeneration appears to be facilitated by excessive acidification of cultures during exponential growth, and by a global regulatory gene responsible for strain degeneration (Kashket and Cao 1995).…”
Section: Introductionmentioning
confidence: 99%
“…with an excess of nutrients and without competition from other organisms, they may lose the ability to produce compounds that would otherwise have been produced under stressful conditions. For example, subcultures of the industrially cultured Gram‐positive, spore‐forming Clostridium acetobutylicum are known to lose their ability to produce the acids for which they are cultured (Kashket & Cao, 1995). This problem of strain degeneration is important when considering Gram‐negative candidate probionts, as unlike some Gram‐positive bacteria they are not endospore‐forming.…”
Section: Probiotic Selection Constraintsmentioning
confidence: 99%
“…In most cases, culturing bacteria on general nutrient media provides the organism with all the essential nutrients to grow and reproduce. However, the ability of bacteria to produce these metabolites can be lost with successive generations (Kashket & Cao, 1995). Further research is required regarding the problem of strain degeneration, particularly its prevention or reduction and, more importantly, its reversal, which would allow for the testing of degenerated candidate probionts.…”
Section: Strain Degenerationmentioning
confidence: 99%
“…One challenge with industrial ABE fermentation by solventogenic Clostridia is strain degeneration due to repeated subculture or continuous fermeantion, which often leads to significantly reduced fermentation efficiency and even predetermined fermentation12. Another cause of strain degeneration is bacteriophage infection due to which many industrial ABE fermentation processes were compromised in early 20th century3.…”
mentioning
confidence: 99%